Phraseological Binomials: A Proposal for Equivalences in English-Spanish Legal Translation - Andrades, Arsenio (Estudios de Traducción, 2016)
Phraseological units are complex structures that may be difficult to comprehend and transfer into other languages due to their idiomatic nature. The translator of English legal texts often comes across binomials, a type of phraseological unit that is a characteristic of this specialized discourse. Based on a specialized comparable bilingual corpus composed of legal forms and agreements, this article identifies several occurrences of this phraseological structure and extracts the most frequent examples in English and Spanish. A contrastive analysis of the data obtained from the corpus helps to establish a series of equivalencies among binomials in both languages and proposes a typology of equivalences regarding these phraseological structures.
Keywords: phraseology; corpus; legal translation; binomials.